Service Quality and Customer Satisfaction in Banking - Thongpoon, Siriluck (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
Service banking is facing several challenges in order to sustain its competitiveness in the long run. In doing so, banks try to promote customer satisfaction especially through service quality. In this situation, interest was aroused to investigate the influence of service quality on customer satisfaction. Questionnaires were randomly distributed to 400 customers of the Government Savings Bank, Cha-aut Branch, Nakhon Si Thammarat. Results revealed that service quality influenced customer satisfaction. In particular, responsiveness, assurance, and reliability were found as key factors significantly and positively influencing customer satisfaction. This could be beneficial to policy makers in other banks or any service sector.